2022
DOI: 10.3390/v14050981
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymorphisms and Genetic Characteristics of the Shadow of Prion Protein Gene (SPRN) in Cats, Hosts of Feline Spongiform Encephalopathy

Abstract: Prion diseases are transmissible spongiform encephalopathies (TSEs) caused by pathogenic prion protein (PrPSc) originating from normal prion protein (PrPC) and have been reported in several types of livestock and pets. Recent studies have reported that the shadow of prion protein (Sho) encoded by the shadow of prion protein gene (SPRN) interacts with prion protein (PrP) and accelerates prion diseases. In addition, genetic polymorphisms in the SPRN gene are related to susceptibility to prion diseases. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Prior reports have shown that several prion-susceptible species, including cattle, sheep, cats, and goats, exhibit a high degree of nonsynonymous polymorphism in SPRN genes, leading to alterations in the amino acid sequence [ 1 , 4 , 5 , 14 , 17 , 22 , 23 , 25 ]. Of note, horses and dogs are prion-resistant species that only have one polymorphism in the SPRN gene [ 6 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior reports have shown that several prion-susceptible species, including cattle, sheep, cats, and goats, exhibit a high degree of nonsynonymous polymorphism in SPRN genes, leading to alterations in the amino acid sequence [ 1 , 4 , 5 , 14 , 17 , 22 , 23 , 25 ]. Of note, horses and dogs are prion-resistant species that only have one polymorphism in the SPRN gene [ 6 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, L-type atypical BSE-affected cattle showed an infrequent sequence variation within the coding sequence of the bovine SPRN gene [ 5 , 6 ] These studies demonstrate a strong relationship between genetic polymorphisms of the SPRN genes and the pathological mechanisms of prion diseases. To date, polymorphisms of the SPRN gene have been examined in prion disease-sensitive and -resistant species [ 1 , 6 , 13 , 14 , 15 , 16 , 17 ]. However, the genetic polymorphisms of the leporine SPRN gene have not been explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found only one insertion/deletion polymorphism in the ORF of the canine SPRN gene. Previous studies have reported that prion-susceptible animals, including cattle, sheep, cats and goats, have highly polymorphic SPRN genes ( 11 , 12 , 21 26 ). In contrast, a prion-resistant animal, the horse, has one polymorphism of the SPRN gene ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in prion-related genes contribute significantly to interindividual variation, so they have been investigated as useful biomarkers in medicine, as well as in the study of pathology, pharmacology, epidemiology, and clinical immunology ( 29 ). In addition, polymorphisms of the SPRN gene in prion disease-susceptible species play a crucial role in determining their susceptibility to prion diseases ( 12 , 30 , 31 ). The SPRN polymorphisms, which contribute to expression level or protein function, show strong associations with the pathogenesis of prion diseases in different species ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%